Combating the Tribo-Corrosion of LDX2404 Lean Duplex Stainless Steel by Low Temperature Plasma Nitriding - Xiaoying Li; Wenbo Dou; Linhai Tian; Hanshan Dong (Lubricants, 2018)
A lean duplex stainless steel, LDX2404, was DC plasma nitrided under a range of treatment conditions. The microstructure characterisation evaluation of the treated samples revealed that a dense, super-hard surface layer can be produced by low-temperature (<450 °C) plasma treatments. The original austenite phase became S-phase and the ferrite phase was supersaturated with nitrogen and ε-Fe3N nitride precipitated from it. When plasma nitriding was carried out at above 450 °C, chromium nitrides precipitated in the surface nitrided layer. Compared to the untreated samples, the surface hardness of the lean duplex stainless steel (DSS) is increased up to four times. The dry wear resistance increased when increasing the treatment temperature. In contrast, the low-temperature treated samples showed the best performance in the electrochemical corrosion and corrosion-wear tests; the performance of the high temperature (>450 °C) plasma nitrided samples was found to be significantly worse than that of the untreated material.